Rereading Virtue In Zarathustra’s Of The Virtue That Makes Small And Of The Chairs Of Virtue - Kahambing, Jan Gresil (Journal of Education and Society, 2018)
From the ‘rhetorical-oratorical’ backdrop of Thus Spoke Zarathustra which denotes a prescriptive calling, this paper rereads the aphorisms that concern the virtues. The book will serve as the main text of the study, aptly because it is regarded as one of Nietzsche’s more mature writings. The paper particularly aims to hermeneutically expose the two aphorisms, namely: Of the Virtue that Makes Small in Book III, and Of the Chairs of Virtue in Book I. It thus confines the study into a particular focus apart from Of Joys and Passions which mainly discusses the ‘nature’ of virtue. Later, the aphorism The Child with the Mirror, which can be found in Book II, will be re-read too as a rejoinder between the two aphorisms of Books I and III. A specific vantage point in this study connotes that there is a seminal thread that connects books III, I, and II – precisely in this order – on the account of what virtue means.